Charismatic leadership: Contribution of Catholic theology of priesthood to leadership model for religious moderation in Indonesia - Tedjoworo, Hadrianus; Nugroho, Benito Cahyo (UIN Sunan Gunung Djati Bandung, 2025)
This study discusses the role of charismatic leadership in the theology of the Catholic priesthood and its contribution to the development of leadership patterns in religious moderation in Indonesia. The main problem raised is the dominance of the hierarchical dimension in the Catholic Church, which can also be found in other religions and tends to ignore the charismatic dimension that can reduce tensions between religious communities. The purpose of this study is to identify theological elements in the Catholic priesthood and charismatic elements that are useful for developing a more inclusive model of religious leadership that supports religious moderation. The methods used were content analysis of literature in Church documents and the views of Catholic theologians, and their correlation with key findings based on qualitative analysis of survey data on charismatic pastoral practices among Catholic priests. Other data used include literature on religious moderation and charismatic leadership theory. The results of this study show that charismatic leadership, inspired by the theology of the Catholic priesthood, provides insight into approaches to religious moderation and reveals great potential at the level of religious leadership to create an atmosphere of peaceful fellowship among religious communities. This leadership model can mitigate interreligious conflicts in Indonesia and offers a new perspective for developing models of religious leadership that are more charismatic than hierarchical, based on an understanding of charisma as a gift from God.